Enalapril: Synthesis and properties - Mijin Dušan Ž.; Stanković Milena; Petrović Slobodan D. (Hemijska Industrija, 2004)
Enalapril was originally synthesized by Merck Sharp and Dohme and is an angiotensin converting enzyme inhibitor. Thus, enalapril is used in the treatment of mild to severe hypertension. Enalapril is chemically (S)-1-[N-[1-(et-hoxycarbonyl)-3-phenylpropyl]-L-alanyl]-L-prolin and although the first synthesis was published in 1980, it can be obtained using different synthetic pathways. This paper describes the synthesis as well as the properties and stability of enalapril.